Controle de convencionalidade por omissão: a responsabilidade do Presidente da República na efetividade dos instrumentos internacionais de Direitos Humanos - Glasenapp, Ricardo Bernd (2015)
This thesis aims to demonstrate the possibility of realization of conventionality control by default in our legal system in the absence of regulations and especially the lack of adaptation of the legal rules existing on Human Rights on the legal innovations arising through treaties international human rights. Faced with such a scenario, this thesis develops having to justify the need for effective human rights within our legal system on the certainty that the simple conclusion of international treaties on human rights is no longer just enough. Once demonstrated the existence of conventionality control by default as a way of realization of human rights by virtue of court decisions, the present thesis switches to the possibility of overcoming the legal problems arising from the legislative omission on human rights through the creation reallocated to the President for legislative initiative to adapt the domestic legal system to international human rights treaties. With such legal innovation presented here, and defends, you can become more effective human rights in our country, without the problem of legislative omission to endure in time unconventional way